TopBP1 and ATR Colocalization at Meiotic Chromosomes: Role of TopBP1/Cut5 in the Meiotic Recombination Checkpoint - Perera, David (The American Society for Cell Biology, 2004)
Mammalian TopBP1 is a BRCT domain–containing protein whose function in mitotic cells is linked to replication and DNA damage checkpoint. Here, we study its possible role during meiosis in mice. TopBP1 foci are abundant during early prophase I and localize mainly to histone γ-H2AX–positive domains, where DNA double–strand breaks (required to initiate recombination) occur. Strikingly, TopBP1 showed a pattern almost identical to that of ATR, a PI3K-like kinase involved in mitotic DNA damage checkpoint. In the synapsis-defective Fkbp6(-/-) mouse, TopBP1 heavily stains unsynapsed regions of chromosomes. We also tested whether Schizosaccharomyces pombe Cut5 (the TopBP1 homologue) plays a role in the meiotic recombination checkpoint, like spRad3, the ATR homologue. Indeed, we found that a cut5 mutation suppresses the checkpoint-dependent meiotic delay of a meiotic recombination defective mutant, indicating a direct role of the Cut5 protein in the meiotic checkpoint. Our findings suggest that ATR and TopBP1 monitor meiotic recombination and are required for activation of the meiotic recombination checkpoint.